Patient backgrounds and short‐term outcomes of complicated appendicitis differ from those of uncomplicated appendicitis. Issue 2 (9th November 2021) - Oba, Takuya; Yamada, Takeshi; Matsuda, Akihisa; Otani, Makoto; Matsuda, Shinya; Ohta, Ryo; Yoshida, Hiroshi; Sato, Norihiro; Hirata, Keiji
Abstract: Background: Appendicitis is classified as either complicated (CA) or uncomplicated (UA). Some authors have shown that the epidemiologic trends of CA and UA may differ. The aim of this study was to clarify differences in backgrounds and surgical outcomes between CA and UA patients. Methods: This study was a cohort study. We extracted case data from the Japanese Diagnosis Procedure Combination (DPC) database from January 2014 to December 2017. Patients were classified into three groups, depending on whether they underwent emergency appendectomy for CA (CA group), emergency appendectomy for UA (UA group), or elective appendectomy (EA group). We evaluated patient characteristics and surgical outcomes for each group. Results: We included 89, 355 adult patients in the study, comprising 29, 331 CA, 48, 691 UA, and 11, 333 EA patients. Old age, larger body mass index, smoking, and medication with antidiabetic drugs, oral corticosteroids, oral antiplatelet drugs, and oral anticoagulant drugs were independent risk factors for CA. The percentage of CA increased with age. In‐hospital mortality (0.15%, 0.02%, and 0.00%) and 30‐d mortality (0.09%, 0.01%, and 0.00%), respectively, of CA patients were significantly higher than those of the UA and EA groups. The duration of postoperative antibiotic administration, duration of fasting, and time before removal of a prophylactic drain were significantly longer in the CA group than in the UA and EA groups. Conclusion: Backgrounds and treatment outcomes of CA and UA patients after emergency surgery are entirely different. Thus, the treatment strategy of CA and UA patients should differ accordingly. Abstract : We show that elderly patients, smokers, and patients with comorbidity are more likely to develop complicated appendicitis (CA), and emergency surgery for CA places the patient at a relatively higher risk than emergency surgery for uncomplicated appendicitis (UA). The importance of this study is that patient backgrounds suggesting the difference in the pathogenesis of CA and UA and surgical outcomes after emergency surgery for CA and UA are shown using a nationwide database.